2022
DOI: 10.3389/fpls.2022.898846
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Silver Nanoparticles on Lemon Growth Performance: Insecticidal and Antifungal Activities of Essential Oils From Peels and Leaves

Abstract: Ten-year-old lemon (Citrus limon L. cv. Eureka) was used during the 2019 and 2020 seasons to investigate the effect of AgNPs at control, 5, 7.5, and 10 mg/L as a foliar application on vegetative growth, yield, and fruit quality. The selected trees were subjected to agricultural practices applied in the field during the study. The results indicated that the foliar application of AgNPs positively improved the shoot length, total chlorophyll, flower, and fruit set percentage, fruit yield, physical and chemical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…Under greenhouse conditions, the foliar applications of Ag-NPs increased chlorophyll content. Several studies found that using Ag-NPs improved the shoot and root systems, the length and width of leaves, the amount of chlorophyll, carbohydrates, proteins, and antioxidant enzymes in bean, wheat, Brassica juncea and lemon [50][51][52]. Moreover, the accumulation of TMV-CP gene reduced in all Ag-NPs treatments and different concentrations compared with TMV infected plants.…”
Section: Discussionmentioning
confidence: 99%
“…Under greenhouse conditions, the foliar applications of Ag-NPs increased chlorophyll content. Several studies found that using Ag-NPs improved the shoot and root systems, the length and width of leaves, the amount of chlorophyll, carbohydrates, proteins, and antioxidant enzymes in bean, wheat, Brassica juncea and lemon [50][51][52]. Moreover, the accumulation of TMV-CP gene reduced in all Ag-NPs treatments and different concentrations compared with TMV infected plants.…”
Section: Discussionmentioning
confidence: 99%
“…Although silver is not an essential element for citrus development, it can cause beneficial effects, such as promotion in vegetative bud development, an increase in total chlorophyll, tolerance to biotic stress, as well as an increase in fruit set percentage [54,55]. Some studies suggest that both the promoter and the phytotoxic effects that AgNPs can generate are related to the Ag ion content and not to the size of the nanoparticles [56]; for example, AgNPs synthesized from extracts of Moringa oleifera Lam.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the levels of amino acids (valine, serine, and aspartate) and the shikimate-phenylpropanoid biosynthesis were down-regulated, while some metabolites of the aspartate pathway increased, suggesting up-regulation of the aspartate family to feed the TCA cycle for energy supply [ 69 ]. Recently, it was found that foliar application of nAg (5, 7.5, and 10 mg L −1 ) can alter the essential oil composition of leaves and peels of lemon trees [ 127 ].…”
Section: Understanding the Impact Of Metal-based Nanomaterials On Pla...mentioning
confidence: 99%